Accessing primary health care services for transition-aged young adults with cerebral palsy; perspectives of young adults, parents, and physicians - Brandon Erin; Ballantyne Marilyn; Penner Melanie; Lauzon Andrea; McCarvill Erin (De Gruyter, 2019)
Young adults with childhood-onset disabilities experience challenges with accessing age appropriate primary health care services as they transition from pediatric to adult health care services. They often experience a negative impact on their health with associated long-term health and social concerns, disease complications and increased use of emergency services once transitioned to adult services. This is particularly challenging for youth with cerebral palsy (CP) due the complexity of their medical needs. The aim of this study was to explore experiences with accessing or providing primary care services for transitioned-aged young adults with CP from young adult, parent, pediatrician and primary care physician perspectives.